Capital Structure and Bank P0erformance: Evidence from Sri Lanka - Durairaj, Binusitha (2010)
The debt-equity mix which determines the optimal capital structure has attracted scholars in the field of financial management. However it has received less attention in the Sri Lankan context thus, this study examines the dynamic effect of capital structure on the performance of nine licensed Sri Lankan commercial banks listed in the Colombo Stock Exchange during the period 2006-2009. Panel data analysis fixed effect model is used to examine the impact of capital structure on Sri Lankan bank performance. Results from this study shows an inverse relationship between debt to equity ratio and debt and performance measures such as return on assets and return on equity and a positive relationship between equity and return on assets and return on equity among Sri Lankan banks. The results thus eliminate the validity of the Modigiliani-Miller argument that capital structure has no effect on the value of the firm, and further also disapprove studies that argue debt increases bank performance. The results also suggest that debt forms a larger proportion of the capital structure and the negative impact of debt overweighs the positive impacts of equity on the performance of Sri Lankan banks.